Suicide risk configuration system in a clustered clinical sample: a generalized linear model obtained through the LASSO technique - Maino, María de la Paz; Morales, Susana; Echávarri, Orietta; Barros, Jorge; García, Arnol; Moya, Claudia; Szmulewicz, Tita; Fischman, Ronit; Núñez, Catalina; Tomicic, Alemka (Revista brasileira de psiquiatria, 2019)
To identify clinical and sociodemographic factors that increase or decrease suicidal risk in a clinical sample of subjects seeking mental health care. A cross-sectional study was performed at three health centers in Santiago, Chile. The Parental Bonding Instrument (PBI), Depressive Experience Questionnaire (DEQ), Outcome Questionnaire (OQ-45.2), Reasons for Living Inventory (RFL), and State Trait Anger Expression Inventory (STAXI-2), in addition to a sociodemographic survey, were applied to 544 participants (333 with suicidal behavior and 211 without current suicidal behavior). Through hierarchical clustering analysis, participants were grouped by similarity regarding suicidal risk. Then, a regression analysis was performed using the Least Absolute Shrinkage and Selection Operator (LASSO) technique, and factors that decrease or increase suicide risk (SR) were identified for each cluster. The resultant clusters were grouped mainly by the age of participants. The most important protective factor was having confidence in one's own coping skills in difficult situations. Relevant risk factors were major depressive disorder (MDD), poor anger management, and difficulties in interpersonal relationships. Suicidal risk manifests differently throughout the life cycle, and different types of bonds may protect from or increase risk of suicide.